Benefits of Vedic learning for improving competence and strengthening mental health - Seriadi, Siluh Nyoman; Candradevi, Dewa Ayu; Avalokitersvari, Ni Nyoman Ayu Nikki (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: The Vedas are an ancient library that is the source or book for the Hindu religion. The Vedas are used as the main guidelines and their teachings are implemented in the daily lives of Hindus. In addition to being a holy book, the Vedas also contain many values contained therein. Tattwam, Susila, and Upakara are three basic frameworks in Hinduism that need to be considered in the 21st century. Method: This research uses a qualitative method focusing on text analysis, which involves in-depth examination of written materials based on their context. The study aims to understand phenomena in their natural settings without manipulation, emphasizing the meaning and quality aspects rather than quantitative measures. Findings: There are many positive benefits of applying the vedic teachings in daily life. By realizing the existence of God, implementing the teachings of Susila and the proper implementation of Upakara in daily life. Not only as a guideline in carrying out the three basic frameworks in Hinduism but there are many other unexpected benefits gained through learning the Vedas, be it in science, character building, making life easier and also in achieving success. Not only as a source of knowledge, but the Vedas are also a source of medicine. This is contained in the Atharva Veda. Conclusion: The benefit of the Vedas that is no less important is that the Vedas are a source of Hindu Law (Dharma). Novelty/Originality of this article: Using qualitative methods focusing on text analysis, this study explores the relevance of the Vedas in everyday life in the 21st century. This research shows that the Vedas not only function as sacred scriptures and sources of knowledge but also provide benefits in character formation, facilitate life, and serve as sources of healing and legal foundation (Dharma) for Hinduism.